Parametric Model Analysis, Geometrical Characteristics and Tool Trajectories to Surface Roughness when Machining the Cycloid Screw by a Five-Axis Milling Machine - Van Bong Pham; Nguyen Van Thien; Van Que Nguyen; Trinh Nguyen Duy; Duy Khanh Nguyen; Dung Hoang Tien (Journal of Machine Engineering)
To improve the screw machining accuracy in modern air compressors. This paper investigates three main issues during the development process for cycloid screw machining methods on five-axis CNC machine tools with high precision and efficiency. First, the theoretical basis of cycloid screw surface shaping and derivative of the final profile equation is established. Then, modeling the center trajectory and feed rate according to the cycloid screw profile is given. Next is the experimental setup and simulation of the cycloid screw machining process and discussions. The obtained surface quality prediction parameters are close to the actual measured value, which can be used as a reference model for five-axis CNC milling technology processes. All experimental results obtained by the proposed mathematical model show that a surface with good surface quality is created, meeting the requirements for surface quality. The main work can be used as references for engineers and technicians in practice.